Evaluasi Pengelolaan Piutang Dagang Dan Penyajiannya Dalam Laporan Keuangan - Rosita, Siti Ita (Jurnal Ilmiah Kesatuan (JIK), 2010)
Credit sales mean the sales which generate cash indirectly. They are useful to increase sales volume and to expand market shares. Accounts receivable emerges fromgoods and services selling on credit and recognized as performed asset in balance. In general, companiesthat conduct credit sales determine non-performed accounts receivable by using reserve or erasing method. The research goal is to find out the recording of accounts receivable arising from credit sales transaction at PT Fajar Harapan and to know how the determination of eliminating non-performed accounts receivable and the presentation of financial accounting run by the company. The author conducted this research at PT Fajar Harapan which operate at automotive sparepart sales and hospital. The results of this research show that PT Fajar harapan is a company conducting credit sales with payment limit in thirty days. PT Fajar Harapan recognizes and records sales transaction at the time of goods are sent to the customers. PT Fajar Harapan has made sales and accounts receivable statement at the end of every period. PT Fajar Harapan does not reserve non-performed accounts receivable with the result that the accounts receivable is reported on the ballance sheet as high as gross realization value. Suggestion for PT Fajar Harapan is the company should makes reserve for non-performed accounts receivable in order that the accounts receivable can be reported as realized net value